Gender differentiation in the analysis of alternative farm mechanization choices on small farms in Kenya - Julliet Wanjiku; John Uhuru Manyengo; Willis Oluoch-Kosura; Joseph T. Karugia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Using multinomial logit we analyze factors that influence the choice of mechanization technologies in Nyanza Province. The results show that farmers are aware of the attributes of the mechanization technologies, and that animal traction is the most commonly used. Gender, formal and informal training of the household head, and technology attributes influence the choice of mechanization technology. This study recommends increased formal and informal training, extension, credit, and tractor hire services to facilitate knowledge transfer, credit, and tractor availability. The study also recommends enactment of laws that increase women's access and control of productive resources.
Keywords: Q12; J16; D80; C81; R29; Q18; 330; mechanization; technology; gender; choice; Agrartechnik; Landwirtschaftlicher Kleinbetrieb; Geschlecht; Kenia; Nyanza